Pengaruh Aktivitas Fisik terhadap Fungsi Kognitif pada Lanjut Usia: Kajian Literatur - Agustana, Rinanda Septiani; Suparto, Tirta Adikusuma; Sumartini, Sri; Purwandari, Asih; Puspita, Wahyoe (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
The problem that occurred in the elderly was a decrease in body function in line with increasing age, one of which was a decrease in cognitive function. Prevention efforts that could be done were by doing physical activity. This study aimed to determine the effect of physical activity on cognitive function in the elderly. The design used in this study was a literature review from database search results that could be accessed through Science Direct, GARUDA, and Google Scholar with articles in the last 5 years (2015-2020). A literature search using the keywords